Disease Distribution in Low-stage Tubo-ovarian High-grade Serous Carcinoma (HGSC): Implications for Assigning Primary Site and FIGO Stage. (July 2018) - Singh, Naveena; Benson, Jack L.; Gan, Carmen; Anglesio, Michael; Arora, Rupali; Faruqi, Asma Z.; Hirschowitz, Lynn; Kommoss, Friedrich; Scott, Kerry; Trevisan, Giorgia; Leen, Sarah Lam Shang; Wilkinson, Nafisa; et al.
Abstract : The latest FIGO and TNM (eighth edition) staging systems for ovarian, tubal, and peritoneal neoplasms require primary site assignment as tubal/ovarian/peritoneal, but provide no guidance or criteria. Fewer than 10% of extrauterine high-grade serous carcinoma (HGSC) cases present at low stage (stage I/II). Low-stage cases offer a unique opportunity to understand the pattern of disease early in its evolution prior to wide dissemination and provide valuable evidence for guiding specimen handling and tumor staging. This study aimed to examine disease distribution in low-stage tubo-ovarian HGSC. Anonymized pathology reports of 152 stage I/II extrauterine HGSCs from 6 teaching hospitals were analyzed: group 1 (n=67) comprised cases with complete tubal examination by Sectioning and Extensively Examining the FIMbriated end of the tube (SEE-FIM) and group 2 (n=85) consisted of cases without documentation of both tubes being fully examined by the SEE-FIM or a SEE-FIM-like protocol. The stage, site/pattern of involvement, site/size of largest tumor focus and laterality of tubal and ovarian involvement were recorded. Tubal mucosal involvement was present in 95% of optimally examined cases and many factors influenced detection of tubal disease. Bilateral involvement, suggestive of metastasis, was significantly more frequent in the ovaries (35%) than the tubes (9%) ( P <0.0001, Fisher exact test). No case showed a complete absence of tubal/ovarian involvement, questioning the biological existence of primary peritoneal HGSC. Disease distribution in low-stage cases supports a tubal origin for most HGSCs. Detailed tubal sampling upstages some apparent stage I cases through detection of microscopic tubal involvement.